Essentials of management - DuBrin, Andrew J. (Mason, OH : Thomson/South-Western, 2006)
Offers a comprehensive, focused, and reader-friendly review of the fundamental principles and applications of effective management, linking theory and practice to prepare students for leadership in today's competitive business environment.
Includes bibliographical references and index.
oif 23/03/15
Loan
Keywords: Management